2012
DOI: 10.1007/s11128-012-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrable quantum computation

Abstract: Integrable quantum computation is defined as quantum computing via the integrable condition, in which two-qubit gates are either nontrivial unitary solutions of the Yang-Baxter equation or the Swap gate (permutation). To make the definition clear, in this article, we explore the physics underlying the quantum circuit model, and then present a unified description on both quantum computing via the Bethe ansatz and quantum computing via the Yang-Baxter equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…As a matter of fact, how to perform quantum computation in integrable systems has been a long-term research project investigated by few groups in mathematical physics. Integrable quantum computation [2] is defined as quantum computation associated with the integrable condition. For example, the integrability condition is the quantum Yang-Baxter equation, so that a multi-particle factorized scattering is identified with a quantum circuit model, where quantum computation without quantum control is considered rather seriously.…”
Section: Discussion: Quantum Computation In Integrable Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, how to perform quantum computation in integrable systems has been a long-term research project investigated by few groups in mathematical physics. Integrable quantum computation [2] is defined as quantum computation associated with the integrable condition. For example, the integrability condition is the quantum Yang-Baxter equation, so that a multi-particle factorized scattering is identified with a quantum circuit model, where quantum computation without quantum control is considered rather seriously.…”
Section: Discussion: Quantum Computation In Integrable Systemsmentioning
confidence: 99%
“…If a quantum computer is an integrable system with control terms, then it seems reasonable to devise appropriate methods to perform information processing tasks. Hence a realistic quantum computer has been naturally assumed to be associated with quantum integrable systems [2].…”
Section: Introductionmentioning
confidence: 99%
“…At the root of our proposal there is the exploitation of Bethe-Ansatz techniques and quantum indistinguishability. Compared to other recent proposals for quantum logic in 1D [77,78,79], our method is more scalable, as it can use the machinery of integrable models, such as the Yang-Baxter relation, to realize composite operations between multiple par-ticles (see also [80,81]). Indeed, since in integrable models all complex n-body scattering effects can be factorized into two-body S matrices, one can straightforwardly apply our findings also in multi-particle scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the YBE is closely related to the generation of quantum entanglement 5 . Furthermore a new quantum computation model based on the notion of integrability was proposed, where the quantum gates are related to unitary solutions of the YBE 6 7 8 .…”
mentioning
confidence: 99%
“…The interest in this form comes from its relation to the braid group which has been recently linked to topological quantum computation 6 7 8 and a scheme for its verification through an optical setup has been proposed 17 and achieved 18 .…”
mentioning
confidence: 99%